TOI-1259Ab – a gas giant planet with 2.7 per cent deep transits and a bound white dwarf companion. Issue 3 (27th July 2021) - Martin, David V; El-Badry, Kareem; Hodžić, Vedad Kunovac; Triaud, Amaury H M J; Angus, Ruth; Birky, Jessica; Foreman-Mackey, Daniel; Hedges, Christina; Montet, Benjamin T; Murphy, Simon J; Santerne, Alexandre; Stassun, Keivan G; et al.
ABSTRACT: We present TOI-1259Ab, a 1.0 R Jup gas giant planet transiting a 0.71 R ⊙ K-dwarf on a 3.48 d orbit. The system also contains a bound white dwarf companion TOI-1259B with a projected distance of ∼1600 au from the planet host. Transits are observed in nine TESS sectors and are 2.7 per cent deep – among the deepest known – making TOI-1259Ab a promising target for atmospheric characterization. Our follow-up radial velocity measurements indicate a variability of semiamplitude K=71 m s^-1, implying a planet mass of 0.44 M Jup . By fitting the spectral energy distribution of the white dwarf, we derive a total age of 4.08^+1.21_-0.53 Gyr for the system. The K dwarf's light curve reveals rotational variability with a period of 28 d, which implies a gyrochronology age broadly consistent with the white dwarf's total age.